Pengembangan Media Pembelajaran Interaktif pada Mata Pelajaran Dasar Desain Grafis Kelas X SMK Antartika 1 Sidoarjo - Ain , Moch. Ibnu; Astuti, Cindy Cahyaning (Indonesian Journal Publisher, 2024)
This research was conducted at SMK Antartika 1 Sidoarjo, Department of Software Engineering. This research is a research and development. This study aims to produce adobe flash-based interactive learning media in the basic subjects of graphic design class X. This research use the ADDIE model which consists of 5 stages, namely (1) analysis; (2) design; (3) development; (4) implementation; (5) evaluation. The trial in this study involved media experts, material experts and small groups (10 students). The results of the value obtained from media experts get a percentage of 91% with the category